Comparison of early and late quality of life between left anterior thoracotomy and median sternotomy off-pump coronary artery bypass surgery. (January 2017) - Nesbitt, Julian J.; Mori, George; Mason-Apps, Charlotte; Asimakopoulos, George
Objective: Minimally invasive coronary artery bypass surgery performed through a left thoracotomy has potential benefits over conventional sternotomy, including reduced surgical trauma, faster recovery and potential improvement in quality of life. This study is a prospective assessment of quality of life in patients undergoing off-pump coronary bypass by median sternotomy and left anterior thoracotomy. Methods: Quality of life was assessed by the EuroQoL questionnaire, with additional questions on dyspnoea, angina, wound pain and scar aesthetics. Outcomes were compared across the data sets at pre-operation, three weeks and three months post-operation. Results: Sixty-six (17 minimally invasive and 49 off-pump) patients (mean age 65±12, 7 females and 59 males) were included. Significant differences in mean EuroQol outcomes were observed for activities, F(1, 64) = 5.86, (p<0.05), pain scores, F(1, 64) = 4.658 (p=0.035) and scar aesthetics, F(1, 64) = 16.83 (p<0.05). There was an additional significant interaction, F(1.898, 121.49) = 3.282, (p<0.05), between time and group for activity levels; exploring this further indicated no significant difference at baseline, but significantly greater improvement observed in the minimally invasive group over time. At 3 weeks, 50% of minimally invasive patients compared to 82% of sternotomy patients (p<0.001) required oral analgesia. At 3 months, 8% of minimally invasive patients and 21% of sternotomy patients (p<0.001) required oral analgesia. Conclusions: Off-pump coronary artery bypass performed with a minimally invasive approach through a left thoracotomy appears to result in earlier improvement in quality of life outcomes compared to conventional sternotomy. These results are important when counselling patients regarding the benefits and difference between a left anterior thoractomy MIDCABG and conventional OPCAB and can be used as pilot data for a larger trial examining differences in the MIDCABG and conventional full sternotomy OPCAB procedures.